Gender Digital Divide and Youth Business Group Leadership - Stein T. Holden; Mesfin Tilahun (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2018)
We assess the gender difference in mobile phone ownership among youth business group members, and how it affects election into leadership and group board positions in recently established rural youth business groups in northern Ethiopia. Based on data on 1125 youths from 119 youth business groups where 32% of the members were female, 37% of the females and 70% of the males owned mobile phones. Male members were twice as likely to become board members and five times as likely to become group leaders. While there was a strong gender effect, having a mobile phone had an even stronger effect enhancing the likelihood of members becoming board members by 17.4 percentage points. Male gender and mobile phone ownership had equally strong effects on members becoming group leaders. Male group members were on average older than female group members, and with there being a significant age effect, this also contributed to the male dominance in group boards and leadership positions. Education also increased the likelihood of members becoming leaders and board members but this did not increase the gender gap in selection into such positions, as females were equally well educated as males.
Keywords: D23; D83; J16; P13; 330; Mobile phone ownership; gender gap; education; group leadership; youth business groups; Ethiopia